SIMULATION STUDY OF LEAN GAS INJECTION INTO RESERVOIR X TO ENHANCE OIL RECOVERY - Mariyana (NIM 22205005), Ririn
ABSTRACT: After primary production of reservoir has done, the oil production depletes and there is residual oil in the reservoir. From the screening test of reservoir depth, fracture gradient, oil viscosity, API gravity, and the driving mechanism of the reservoir, it is found that the lean gas injection is appropriately applicable to enhance the oil recovery from the reservoir. The objectives of this thesis are to study the sensitivity of all affecting parameters of lean gas injection and to obtain the recovery increment after the injection. The methodology of this research are to run a sensitivity test to the reservoir model which are grid blocks, the perforation length of production and injection wells, and the sensitivity of the production parameters including BHP, composition of lean gas and rate of injection. The results from this research are affecting parameters of lean gas injection are perforation length of production and injection wells, BHP, composition of lean gas and rate of injection. The highest recovery increment after injection is 7.52percent.